Application of the Problem Based Learning Model to Communication Skills and Mathematical Problem Solving Skills in Junior High School Students - Anam, Khaerul; Sudarwo, Raden; Wiradharma, Gunawan (JTAM (Jurnal Teori dan Aplikasi Matematika), 2020)
This study aims to find out: (1) the influence of the use of the Problem-Based Learning (PBL) model on the mathematical communication skill; (2) the influence of the use of the Problem-Based Learning (PBL) model on the mathematical problem-solving skill. This study was conducted on class VIII. The research design is pre-post quasi experimental design. Samples were selected using the cluster random sampling technique. The employed instrument in this study was an essay test. The obtained data were then analyzed using independent samples t-test and simple linear regression. The results indicated that (1) the average score of students' mathematical communication skills taught by problem-based learning models was higher than those taught by conventional methods; (2) the average score of students' mathematical problem-solving abilities taught by problem-based learning models is higher than students taught by conventional methods